Pemilihan Platform Strategi Pemasaran pada Industri Manufaktur dan Jasa dengan Metode AHP - Pratiwi, Irnanda; Andalia, Winny; Ghafar, Muhammad Sandy (JATI UNIK : Jurnal Ilmiah Teknik dan Manajemen Industri, 2025)
Indonesia is experiencing an economic revival marked by rising consumption of goods and services, particularly in the food industry sector, which reached 1,542,410 units (48.3%), highlighting its crucial role in the national economy. However, Micro and Small Industries (IMK) still face challenges such as limited capital, resources, and suboptimal digital marketing strategies. This study aims to determine the most effective digital marketing strategy priorities to enhance IMK competitiveness. Data were obtained from BPS (2021) and interviews with business actors in Palembang, using the K-Means clustering method for innovation segmentation and the Analytical Hierarchy Process (AHP) for strategy selection. The results show that Java Island achieved the highest innovation score (11,692), dominated by marketing and distribution (6,265) and product innovation (4,440). The KBLI 10–22 sector excelled with a score of 6,336, while ANOVA testing (Sig. = 0.000) indicated significant differences between clusters, with marketing emerging as the dominant factor (F = 116.544). The descriptive application criterion (0.413) and social media platform (0.7) were identified as the most effective strategies. This study concludes that digital innovation and interactive descriptive content play key roles in improving IMK marketing performance and contribute to strengthening regional innovation literature and technology-based digital marketing strategies.